The Difference in Interleukin-12 (IL-12) on Degrees of Acne Vulgaris Severity - Hendra Tarigan Sibero; Eryati Darwin; Yan Wirasati; Satya Wydya Yenny; Suharmanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Acne vulgaris (AV) is a common disorder of pilosebaceous seen mainly in adolescents. Most cases of AV present with a pleomorphic lesion array, consisting of blackheads, papules, pustules, and nodules of varying severity. Acne is one of the three most common skin disease, especially in adolescents and young adults, with an estimated prevalence of 85% (aged 12-25 years). Acne vulgaris (AV) is still a health problem in the world and Indonesia. The causes of AV are multifactorial and can lead to various complications. Aim: This study looked for the difference in interleukin-12 (IL-12) on degrees of AV severity. Materials and Method: This study was an observational analytic study with a cross-sectional approach. The research was conducted at the Diniyah Putri Islamic Boarding School, Lampung Province, Indonesia, in August 2020. The independent variable in this study was the AV degree, while the dependent variable was the IL-8 level. The sampling method in this study was consecutive sampling, as many as 63 AV patients. The research material is serum from venous blood. Examination of interleukin-8 levels using the ELISA method. Data analysis was univariate to find the mean and standard deviation of IL-8 levels, as well as the frequency distribution to determine the degree of AV. While the bivariate analysis was to determine the difference in the mean of IL-8 levels in AV patients. Results: The mean age of the respondents was 15.49 ± 1.07 years, the mean IL-12 level was 48.22 ± 15.62 and most of the AV degrees were in a severe category as much as 61.9%. Conclusion: Statistically there is no difference in the mean IL-12 levels in moderate and severe AV patients, but IL-12 levels are higher at severe AV degrees than moderate AV degrees.